2022
DOI: 10.18240/ijo.2022.07.07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of minimally invasive glaucoma surgery with trabecular micro-bypass stent and microhook ab interno trabeculotomy performed in conjunction with cataract surgery

Abstract: AIM: To evaluate the effectuality and safety of cataract surgery combined with either ab interno trabeculotomy by the microhook (μLOT) or a single iStent® trabecular bypass implantation (iStent) in eyes with cataract and mild-to-moderate glaucoma. METHODS: This study enrolled subjects with mild-to-moderate open angle glaucoma with visually significant cataract who used two or more ophthalmic antiglaucoma agents between 60 and 90y of age. Patients underwent cataract surgery cooperated with either implantation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, these studies reported values of 12.7 mmHg or 14.0 mmHg for the final IOPs. In contrast, procedures in open-angle glaucoma patients who underwent the μLOT-Phaco procedure were found to have a baseline IOP of 16.7 mmHg followed by a 17.8% reduction in the IOP reduction and with a final IOP of 13.6 mmHg (7). The IOP reduction rate and final IOP in the iStent-Phaco and μLOT-Phaco groups in our study were 10.0% and 13.2 mmHg, and 16.2% and 13.2 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, these studies reported values of 12.7 mmHg or 14.0 mmHg for the final IOPs. In contrast, procedures in open-angle glaucoma patients who underwent the μLOT-Phaco procedure were found to have a baseline IOP of 16.7 mmHg followed by a 17.8% reduction in the IOP reduction and with a final IOP of 13.6 mmHg (7). The IOP reduction rate and final IOP in the iStent-Phaco and μLOT-Phaco groups in our study were 10.0% and 13.2 mmHg, and 16.2% and 13.2 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Surgical outcomes have been evaluated between μLOT and iStent combined with cataract surgery (6,7) and between goniotomy with Kahook Dual Blade (KDB) or iStent combined with cataract surgery (8) in two previous retrospective studies. Equal or less effectiveness was found for iStent procedures with cataract surgery as compared with μLOT or KDB procedures with cataract surgery.…”
Section: Discussionmentioning
confidence: 99%